Species awareness days: Do people care or are we preaching to the choir?. (March 2021) - Chua, Marcus A.H.; Tan, Audrey; Carrasco, Luis Roman
Abstract: Biodiversity awareness days are awareness-raising interventions of increasing popularity. But what makes an awareness day campaign successful has been overlooked. We sought to determine (1) if species or taxa awareness days led to awareness proxied by engagement for information, (2) if some awareness days were more effective than others, and the possible reasons for success, and (3) if awareness days led to positive conservation action. Google Trends and Wikipedia page views of the subject of biodiversity awareness days with a history of at least five years were compiled and analyzed. For 16 awareness days examined, there was an average of 3.07% increase in Google searches and 34.0% increase in Wikipedia page views. Awareness days for pangolin, polar bear, turtle, and tiger (25% of taxa) had significant increases in both metrics, and 43.8% of taxa had success in at least one metric. Over half of taxonomic groups, which include species considered charismatic and appealing, saw no clear increase in information-seeking behavior. Tweets containing a call to action had a positive relationship with the number of retweets. Some awareness days appeared to correspond to an increase in conservation fund-raising for advocacy groups and charities that participated in the event. Overall, the results suggest that resources diverted to promoting awareness days might be better allocated to less popular threatened species, and that advocacy groups and charities may want to consider optimizing their messages and participation to maximize benefits of these events. Graphical abstract: Unlabelled Image Highlights: We studied species awareness day web search, Twitter sharing, and donations. 43.8% of species saw a rise in information seeking behavior on their awareness day. Most taxa, largely charismatic species saw no significant event search changes. Charities that reported more event donations matched taxa with event search rise. Resources for promoting events might be better allocated to less popular species.